1998
DOI: 10.1111/j.1532-950x.1998.tb00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations and Cardiovascular Influence of Lidocaine Infusions During Isoflurane Anesthesia in Healthy Dogs and Dogs With Subaortic Stenosis

Abstract: Methods shown in the study can be used in clinical cases to achieve therapeutic lidocaine levels without significant cardiovascular depression during isoflurane anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…Nunes de Moraes et al . [23] reported there were not any detrimental cardiovascular effects related to an infusion of lidocaine at 7.2 mg/kg/hr during isoflurane anesthesia in healthy dogs or dogs with aortic stenosis. Matsubara et al [20] reported that lidocaine infusions (3 and 12 mg/kg/hr CRI following 2 mg/kg IV) did not induce clinically significant changes in heart rate and arterial blood pressure in dogs anesthetized with sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…Nunes de Moraes et al . [23] reported there were not any detrimental cardiovascular effects related to an infusion of lidocaine at 7.2 mg/kg/hr during isoflurane anesthesia in healthy dogs or dogs with aortic stenosis. Matsubara et al [20] reported that lidocaine infusions (3 and 12 mg/kg/hr CRI following 2 mg/kg IV) did not induce clinically significant changes in heart rate and arterial blood pressure in dogs anesthetized with sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, lidocaine plasma concentrations greater than 15 µg mL −1 cause bradycardia, vasodilation, and negative inotropy (Stoelting 1991). In one study of lidocaine toxicity in dogs, plasma concentrations of 2.7–5.27 µg mL −1 did not change arterial blood pressure, cardiac index, systemic vascular resistance, or electrical rhythm (DeMoraes et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine’s ability to reduce halothane, isoflurane and enflurane MAC has been reported in humans, horses, dogs and cats (Himes et al. 1977, 1979; Doherty & Frazier 1998; Moraes et al. 1998; Muir et al.…”
Section: Introductionmentioning
confidence: 98%